Characterization of Microplastic Degrading Indigenous Bacteria from Ambon Bay Waters - Zakaria, Idham Halil; Siswanto, Dian; Mustafa, Irfan (Bogor Agricultural University, Indonesia, 2024)
Microplastic degradation by bacteria can degrade low-density polyethylene (LDPE). This study aimed to analyze the potential of Ambon Bay bacteria for microplastic degradation, the condition of microplastics after degradation, and identification of the potential for microplastic degradation. The results of isolation revealed as many as 20 bacterial isolates, which correlated with physicochemical conditions in the waters of Ambon Bay. Nine of them could degrade microplastics as indicated by the presence of a clear zone, namely KA1, KA2, KA3, KA4, KA5, KA9, KA10, KS6, and KS8. They were checked for biofilm formation, microplastic hydrophobicity, and percentage of microplastic weight reduction. Four isolates with the highest percentage of microplastic weight reduction on day 40 were KA1, KA2, KA3, and KA10 at 36.19%, 10.16%, 28.39%, and 17.07%, respectively. The results of LDPE microplastic degradation showed differences using field emission scanning electron microscopy-energy dispersive spectroscopy (FESEM/EDS), attenuated total reflection-fourier transform infrared (ATR-FTIR), and X-ray diffraction (XRD). The bacterial isolates identified were KA1 (Bacillus cereus), KA2 (Bacillus toyonesis), KA3 (Bacillus paramycoides), and KA10 (Escherichia coli). Indigenous bacteria from the waters of Ambon Bay have the potential to degrade LDPE microplastics, which causes structural changes, decreased crystallinity, weight, and C=C groups in microplastics after degradation, with bacterial isolate KA1 identified as Bacillus cereus showing the best potential with degradation of LDPE microplastics by 36.19%.